PENGEMBANGAN JEJARING INOVASI DAN PELAKSANAAN SURVEI PASAR PRODUK INOVATIF - Rayna Kartika; Dian Yuni Anggraeni; Ares Albirru Amsal (Jurnal Hilirisasi IPTEKS, 2021)
Business development requires research and networking. Even in their infancy, business owners need these things. It is just that often Technology-Based Beginner Entrepreneurs (PPBT) do not take this seriously. This activity's long-term goal is to create market surveys and networks that provide convenience in developing the PPBT business. The specific targets of this activity are: 1) conducting a market survey for Andalas University PPBT products (minimum 5 products); 2) implementation of business matching where PPBT is met with all stakeholders, especially business people who are relevant for the development of PPBT products as well as with buyers who can become buyers for PPBT products. The method used is by conducting market surveys to potential customers and conducting business meetings that bring together PPBT and all parties who can help PPBT business. The output of this activity is a market survey and business meeting. The activities obtained were marketing innovative products such as mangosteen peel teabags, Unca tea (Gambir) teabags, sorghum flour, honey peel-off masks, and coffee body scrubs are still tricky. This is because the production of this innovative product is not carried out continuously, and the selling price is relatively high compared to similar comparison products. It can be concluded from this activity that Unand's innovation product must compete with other products if it is to be chosen by the community. One form of strategy that can be done is to reduce production costs so that the selling price of the product can also be reduced. Another form of increasing sales of innovative products is by producing break-even points so that producers will not suffer losses.